The EU perspective not for Sarajevo? Bosnia and Herzegovina’s integration with the European Union: opportunities, challenges and perspectives - Szynol, Monika (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
In 2018 the European Union (EU) recalled that the future of the Western Balkans lies in the EU. The vision of an “European (Union) future” was announced to the Balkan countries fifteen years earlier, in 2003, when they were recognized as a potential candidates for membership in the EU. In 2016 Sarajevo decided to apply for membership in the European Union. Therefore, the main aim of this article is to analyse the possibility of joining the EU by Bosnia and Herzegovina. It is necessary to identify – even if chosen – opportunities and challenges, perspectives and barriers on the path to further integration of that country with Brussels. The background of these considerations must be the EU’s policy towards the Western Balkans region, which lost its dynamics with the beginning of the second decade of the 21st century, and is trying to retrieve if for various reasons nowadays. Will Bosnia and Herzegovina benefit from the intensification of the EU’s enlargement policy?

W 2018 roku Unia Europejska (UE) przypomniała, że przyszłość Bałkanów Zachodnich znajduje się w UE. Perspektywa „europejskiej (unijnej) przyszłości” została zaprezentowana państwom bałkańskim już piętnaście lat wcześniej, w 2003 roku, kiedy to zostały one uznane za państwa potencjalnie kandydujące do członkostwa w UE. W 2016 roku Sarajewo zawnioskowało o akcesję do Unii Europejskiej. Głównym celem niniejszego artykułu jest zatem analiza możliwości przystąpienia Bośni i Hercegowiny do UE. Niezbędne jest zidentyfikowanie – chociażby wybranych – szans i wyzwań, perspektyw i barier na drodze do dalszej integracji tego państwa z Brukselą. Tłem dla rozważań musi stać się polityka Unii Europejskiej wobec regionu Bałkanów Zachodnich, która straciła na dynamice wraz z początkiem drugiej dekady XXI wieku, by w jej końcu próbować ją (z różnych względów) odzyskać. Czy na intensyfikacji polityki rozszerzenia UE może skorzystać Bośnia i Hercegowina?
Integracja Bośni i Hercegowiny z Unią Europejską: szanse, wyzwania i perspektywy
Keywords: The European Union; the EU enlargement policy; Bosnia and Herzegovina; Western Balkans; Unia Europejska; polityka rozszerzenia UE; Bośnia i Hercegowina; Bałkany Zachodnie